2018
DOI: 10.1111/sms.13252
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic impact of football training in 55‐ to 70‐year‐old women and men with prediabetes

Abstract: The effects of football training on bone health were examined in 55- to 70-year-old sedentary women and men with prediabetes. Patients (n = 50) with prediabetes (age; 61 ± 9 years, BMI 29.7 ± 0.6 kg/m , body fat content; 37 ± 1%, VO ; 22.7 ± 0.8 mL/min/kg and mean arterial pressure; 104 ± 3 mm Hg) were randomized into a football training group (FTG; n = 27, 14 women) and a control group (CON; n = 23, 11 women). At baseline, 73% and 24% were diagnosed with femur osteopenia and osteoporosis, respectively. FTG pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
(109 reference statements)
0
25
0
Order By: Relevance
“…Of note, some studies, which we excluded after our preliminary full-test analysis because they include non-osteoporotic study groups, monitored the benefits of physical activity on bone metabolism by the evaluation of P1NP and CTX, the two biomarkers considered specific for bone turnover (44,48). Interestingly, an improvement in bone metabolism was induced by different types of exercise, for example a football training intervention (49,50). Moreover, Moreira et al found a positive effect of high-intensity aquatic exercise on P1NP and CTX among people with osteoporosis and osteopenia on P1NP and CTX (51).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, some studies, which we excluded after our preliminary full-test analysis because they include non-osteoporotic study groups, monitored the benefits of physical activity on bone metabolism by the evaluation of P1NP and CTX, the two biomarkers considered specific for bone turnover (44,48). Interestingly, an improvement in bone metabolism was induced by different types of exercise, for example a football training intervention (49,50). Moreover, Moreira et al found a positive effect of high-intensity aquatic exercise on P1NP and CTX among people with osteoporosis and osteopenia on P1NP and CTX (51).…”
Section: Discussionmentioning
confidence: 99%
“…of rest in between, and the average was used as the test result. Height, weight, body fat percentage, and muscle mass were measured using a Body Composition Analyzer (InBody 270, Seoul, South Korea) [24]. The participants were instructed to remove their socks and step on the scale with their feet aligned with the foot electrodes while holding the handle with thumbs placed on the oval electrodes and arms straight out from the body.…”
Section: Methodsmentioning
confidence: 99%
“…Football training performed 2–3 times per week for 3–4 months has been shown to improve femoral shaft and trochanter BMD in healthy, sedentary, middle‐aged women 16 and femoral neck and femoral shaft BMD in middle‐aged men and women with prediabetes, 17 and to improve tibial BMD, jump power and muscle strength in healthy, untrained, premenopausal women 18 . In the latter study, further positive effects on bone mineralization and muscle strength was reported after 16 months of football 19 …”
Section: Introductionmentioning
confidence: 99%